C-107 Stigma and depression among newly diagnosed HIV infected MSM in China. (January 2016) - Tao, Jun; Wang, Lijuan; Kipp, Aaron; Qian, Han-zhu; Yin, Lu; Ruan, Yuhua; Shao, Yiming; Lu, Hongyan; Vermund, Sten
Abstract : HIV-related stigma is a risk factor for depression among persons living with HIV, but this has not been studied in persons who are newly diagnosed. Men who have sex with men (MSM) are vulnerable to depression and/or anxiety due to their identity as members of a discriminated minority group, potential social isolation, and, frequently, high risk of HIV acquisition. We evaluated the stigma-depression association among newly diagnosed HIV-infected Chinese MSM in Beijing. Methods: We recruited 366 MSM who were newly diagnosed in the baseline survey of a randomized clinical trial. HIV-related stigma was measured by a scale constructed with sensitivities towards Asian culture. Exploratory factor analysis helped validate the scale. Depression was assessed from the Hospital Anxiety and Depression scale (HADS). Depression was categorized as normal, borderline, and suspicious. Multivariable ordered logistic regression was used to assess the association between continuous stigma scores and depression. Results: The HADS classified 30% of participants as depressed. The HIV-related stigma scale proved valid, and 4 subscales were replicated in the exploratory factor analysis. Median scores for enacted, felt, vicarious, and internalized stigmas were 0, 17, 2, and 5, respectively. One point increase of stigma scores was associated with a 3% to 9% increase in the odds of being depressed, with internalized stigma (shame, guilt, contact avoidance) having the strongest association (aOR = 1.09, 95% CI: 1.07 to 1.12). Conclusions: HIV-related stigma was a risk factor for depression among newly diagnosed HIV-infected MSM. Interventions for coping with internalized stigma following HIV diagnosis may reduce depression and improve downstream indications of the care continuum: linkage to care, retention, and adherence to antiretroviral therapy.